Initial Performance of Virginia's Interstate 81 In-Place Pavement Recycling Project. Issue 1 (January 2015) - Diefenderfer, Brian K.; Bowers, Benjamin F.; Apeagyei, Alex K.
Rehabilitating or reconstructing existing asphalt pavements by applying in-place pavement recycling techniques has been shown to be more cost-effective and more environmentally friendly than with traditional techniques. However, the scanty information in the literature documenting the structural and functional performance of these processes for high-volume roadways, leads to a perception by pavement engineers that the techniques are suitable only for lower-volume roads. This paper presents performance data for the 3.66-mi section of Interstate 81 in Virginia that was rehabilitated through the use of full-depth reclamation, cold central-plant recycling, and cold in-place recycling during the 2011 construction season. The performance data used to document the pavement condition included the structural capacity obtained by a falling-weight deflectometer and rut depth and ride quality measurements collected by an inertial profiler. The structural layer coefficients for the recycled materials were at the upper range of values reported in the literature. The pavement sections continued to perform well in regard to their functional and structural condition after the application of approximately 6 million equivalent single-axle loads and nearly 3 years of service. Two sections with different overlay thicknesses in the right lane also performed well after nearly 3 years of service.